The Theology of Henry David Thoreau - Guttappa B., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2023)
Henry David Thoreau (1817-1862), a representative of the American Transcendentalist, took to new paths in his exploration of individual and cosmic consciousness. It is quite interesting to see that 'Transcendentalism' was always linked with the 'Context'. This context is always understood by their rebellion against the contemporary situation. The act of insurgence makes them different from others. In attempting to define the transcendentalism, it can be said that transcendentalists belonged to a particular generation who did attempt to redefine a few terms like religion and spirituality in a new way; in a new light. The period of transcendentalism was also marked by experimentation and logical thinking. It emerged as a voice against the conservative institutions. Thoreau was also greatly influenced by the wisdom of Indian philosophy. This article will interpret Thoreau's works and bring to light its mystical and spiritual elements.
Keywords: Transcendental; existence; mysticism; experiment; materialistic and spiritual